(untitled) (Journal of Parents and Teachers, 2025)
The article refers to elderly people and the respect that some individuals have merely because they are older and have beards, drawing a parallel to teachers. It also highlights that, a few years ago, students admired their professors, whereas now they are much more distanced from this reality.